2009
DOI: 10.1590/s0034-89102009005000048
|View full text |Cite
|
Sign up to set email alerts
|

Consumo de frutas e hortaliças por idosos de baixa renda na cidade de São Paulo

Abstract: OBJECTIVE:To estimate the socioeconomic and sociodemographic factors associated with the daily intake of five servings of fruit and vegetables by elderly individuals living in low income areas, identifying the main fruits and vegetables which compose the diet of this population.METHODS: This is a cross-sectional population-based study with 2,066 low income elderly individuals (≥60 years) living in the city of São Paulo, Southeastern Brazil, in 2003. To assess the fruit and vegetable intake a Food Frequency Qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
32

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 18 publications
1
16
0
32
Order By: Relevance
“…No comparisons were carried out with the BMI of elderly people. Viebig et al (2009) 32 also found similar results for intake among 2,066 elderly residents in Sao Paulo: only 19.8% reported daily consumption of fi ve or more servings of FV. The study also cites other literature results, with reports of adequate consumption in about 20% of the elderly population only in the city of São Paulo.…”
Section: Adults and Elderlysupporting
confidence: 63%
“…No comparisons were carried out with the BMI of elderly people. Viebig et al (2009) 32 also found similar results for intake among 2,066 elderly residents in Sao Paulo: only 19.8% reported daily consumption of fi ve or more servings of FV. The study also cites other literature results, with reports of adequate consumption in about 20% of the elderly population only in the city of São Paulo.…”
Section: Adults and Elderlysupporting
confidence: 63%
“…O nível de escolaridade identificado foi o curso superior completo (32,5%). A renda familiar foi caracterizada entre 2 a 3 salários mínimos (37,5%), indicando que o crescimento do consumo de hortaliças ocorre quando há um aumento da renda das famílias, concordando com Viebig et al (2009), que observaram que cerca de 35,0% dos idosos de baixa renda em São Paulo não consumiam diariamente nenhum tipo de fruta ou hortaliça, em função do preço mais elevado se comparado a uma refeição constituída por alimentos mais populares, a exemplo do arroz e feijão. Silva (2013) também comprovou que a decisão de consumo de frutas e hortaliças está relacionada com o nível de renda familiar, com notável discrepância entre os domicílios pobres e ricos, sendo que produtos como alface, repolho, cenoura, beterraba e tomate está fora das possibilidades dos lares mais pobres, principalmente pelo alto valor e insuficiência de renda.…”
Section: Resultsunclassified
“…Estar desnutrido, como observado, provavelmente é consequência de um inadequado consumo alimentar de todos grupos de alimentos, não apenas de frutas. 28 No que se refere às frutas mais consumidas, no estudo de Viebig et al 29 foram encontrados resultados semelhantes: banana (41,0%), laranja (30,4%); e as frutas nunca consumidas foram abacaxi (87,0%) e abacate (94,5%). As escolhas por essas frutas podem ser decorrentes de fatores como dificuldade de mastigação, preço, disponibilidade, acesso físico e orientações médicas, que, consequentemente, interferem na ingestão alimentar.…”
Section: Discussionunclassified